The MICADO Integrated Gamma Station for Radioactive Waste Packages radiological characterization - Lepore L.; Gandolfo G.; Marzo G.A.; Cherubini N.; Casagrande D.; Palumbo E.; Ratto N.; Fanchini E.; Pepperosa A.; Giordano F.; Morichi M. (EPJ Web of Conferences, 2023)
The MICADO (Measurement and Instrumentation for Cleaning And Decommissioning Operations) Project of the H2020 Research and Innovation Programme aims to propose a cost-effective solution for non-destructive characterization of nuclear waste, implementing a digitization process that could become a referenced standard facilitating and harmonizing the methodology used for the in-field Waste Management and Dismantling & Decommissioning operations. It employs instruments based on different technologies: an active and passive neutron measurement system, a photo-fission facility, and the ‘Integrated Gamma Station’. Within the MICADO Project, an entire work package has been dedicated to the design and realization of the ‘Integrated Gamma Station’ obtained by combining different gamma detection technologies supporting each other to a comprehensive and effective non-destructive gamma characterization, able to accommodate Radioactive Waste Packages of different sizes. The techniques implemented are i) dosimetry measurements, count rate inspection and raw spectroscopy with the CAEN RadHAND, ii) gamma imaging in open geometry with the CEA Nanopix gamma camera, iii) high resolution gamma spectrometry with the ENEA Tomographic Gamma Scanner (TGS). The latter able to carry out different characterization methodologies, i.e., Open Geometry, Segmented Gamma Scanning, Angular Scanning, and Tomography. This paper describes the layout of the Integrated Gamma Station conceived, its features and detection capabilities, and part of the measurement campaign realized during the MICADO Project.